Sight settings for archers shooting up and down hills - Park, J. L. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2025)
Field archery is conducted on an archery course similar in layout to a golf course. Archers shoot at targets placed one after another, usually involving the archers shooting up, down and across slopes. Archers need accurate sight settings if they are to obtain high scores. However, the required sight settings for slopes differ from those on flat ground. One method used by archers is to set the sight to the horizontal distance to the target (the `rifleman`s rule`). It has been shown that method does not provide the required precision. It has also been shown that a simple `percentage distance cut` is not viable. An alternative method is provided.